Εντοπισμός και διάσωση αλλοδαπών από τη βραχονησίδα ''ΜΑΝΔΗΛΟΥ'' Στενού Καφηρέα την 01-11-2022 (HellenicCoastguard, 2022)
: Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE